2005
DOI: 10.1354/vp.42-1-52
|View full text |Cite
|
Sign up to set email alerts
|

Metastatic Tumors to the Adrenal Glands in Domestic Animals

Abstract: Abstract. Although metastases to the adrenals are common in humans, they have not been thoroughly studied in animals. The purpose of this retrospective study was to document the types of malignant tumors that metastasize to canine, feline, equine, and bovine adrenals, and the rate at which they do so. The average rate of adrenal involvement in metastatic cancer was 112/534 (21.0%) in dogs, 12/81 (14.8%) in cats, 18/67 (26.9%) in horses, and 5/16 (31.3%) in cattle. In dogs, 26 different tumor types metastasized… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(56 citation statements)
references
References 23 publications
1
50
1
4
Order By: Relevance
“…Common tumor types that metastasize to the adrenal gland include carcinoma, adenocarcinoma, and lymphoma. Only one dog was reported to have developed Addison's disease secondary to the metastatic neoplasia [12]. Necropsy findings in this doe revealed that the metastatic adenocarcinoma originated from the uterus and infiltrated multiple abdominal organs.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Common tumor types that metastasize to the adrenal gland include carcinoma, adenocarcinoma, and lymphoma. Only one dog was reported to have developed Addison's disease secondary to the metastatic neoplasia [12]. Necropsy findings in this doe revealed that the metastatic adenocarcinoma originated from the uterus and infiltrated multiple abdominal organs.…”
Section: Discussionmentioning
confidence: 85%
“…Histological examination of the adrenal glands after euthanasia revealed highly anaplastic bilateral adrenal neoplasia. According to a recent retrospective study, the average rate of metastatic involvement of the adrenal glands is 21% in dogs, 26.9% in horses, and 31.3% in cattle [12]. No goat necropsies were involved in that study.…”
Section: Discussionmentioning
confidence: 98%
“…Tumores primários foram mais prevalentes (75,7% dos casos de neoplasma). As adrenais foram sítios de metástase em nove cães (24,3% dos casos de neoplasma), incidência semelhante ao que é reportado na literatura (Labelle & De Cock 2005).…”
Section: Discussionunclassified
“…Os demais tumores metastáticos foram: osteossarcoma, melanoma, linfoma, colangiocarcinoma, sarcoma histiocítico e adenocarcinoma pulmonar. Foi reportado que em 40,2% dos casos as metástases são encontradas na avaliação macroscópica das adrenais de cães, o restante é detectado apenas durante a avaliação histológica (Labelle & De Cock 2005). Neste estudo, em 77,8% dos cães com metástases, essas só foram visualizadas histologicamente.…”
Section: Discussionunclassified
“…Main findings in affected dogs were severe lymphoplasmacytic inflammation and atrophy of all layers of the adrenal cortex (FRANK et al, 2013). Other rare causes included granulomatosis destruction, amyloidosis, hemorrhage, metastatic neoplasm (LABELLE; DE COCK, 2005;RO-CKWELL et al, 2005;REUSCH et al, 2007;FRANK et al, 2013) and the use of drugs as mitotane and trilostane which induce the adrenal glands necrosis (REUSCH et al, 2007).…”
Section: Introductionmentioning
confidence: 99%